Intercomparison of the expected change in the temperature and the precipitation retrieved from CMIP6 and CMIP5 climate projections: A Mediterranean hot spot case, Turkey - Bağçaci, S. Çağatay; Yucel, Ismail; Duzenli, Eren; Yilmaz, M. Tuğrul (Atmospheric research, 2021)
The performances of a large number of Global Circulation Models (GCMs) belonging to the latest release the Coupled Model Intercomparison Project phase 6 (CMIP6) in comparison with its predecessor CMIP5 are evaluated for monthly precipitation and temperature over Turkey (i.e. climate change hotspot). The ensemble of best top four models from both CMIP simulations is also used to investigate the future climate change under medium and high emissions for short, medium, and long terms. Results show CMIP6 products outperform CMIP5 in terms of accuracy statistics, particularly for precipitation. Overall, CMIP6 indicate less intermodel variability, implying the climate signal obtained via CMIP6 is improved relative to CMIP5. The CMIP6 reduce the error in precipitation and temperature 11% and 6%, respectively while increasing the correlation 13% for precipitation. Correlation is not changed for temperature. The substantial success of CMIP6 mainly manifests itself in the winter precipitation and autumn temperature. A slightly warmer (up to 0.35 °C) climate from the CMIP6 is projected while precipitation change in mean precipitation decline is about 2.5% smaller for CMIP6. However, precipitation changes in maximum decline and increase are more noticeable for CMIP6, addressing the better resolving for future climate variability. The summer warming (up to 6.5 °C) and drying (up to −40%) towards autumn spread across the country. The increased precipitation projection in the winter and spring over the east of the Black Sea Region and north-east of Anatolia may further increase the flood risks in the area. •Precipitation and temperature derived from CMIP6 GCMs are comparatively evaluated with CMIP5 GCMS.•A large number of model evaluations from both CMIP simulations are performed.•Change in climate under different scenarios and periods over Turkey (climate hot spot) are evaluated.•Sensitivity of CMIP6 for extreme climate variables is displayed.